Real exchange rates, preferences, and incomplete markets: Evidence, 1961-2001 - Allen C. Head; Todd D. Mattina; Gregor W. Smith (Queen's University, Department of Economics, 2004)
Many international macroeconomic models link the real exchange rate to a ratio of marginal utilities. We examine this link empirically, allowing the marginal utility of consumption to depend on government expenditure, real money balances, or external habit. We also consider two environments with incomplete asset markets; one with exogenously missing markets but an endogenous discount rate that anchors the distribution of wealth and one with endogenous market segmentation. Although none of these satisfies theoretical and over-identifying restrictions for every country, utility with external habit persistence provides the best match with real exchange rates for OECD countries between 1961 and 2001.
Keywords: F41; 330; real exchange rate; consumption; marginal utility